Strategy For Developing The Tambasa Nagari Guguak Malalo Tourist Attraction In The Southern Batipuh District Of Tanah Datar Regency - Rika Andriani; Yuhendra Yuhendra (Menara Ilmu : Jurnal Penelitian dan Kajian Ilmiah, 2026)
AbstractThis study aims to identify appropriate development strategies for the Tambasa tourist attraction located in Nagari Guguak Malalo, South Batipuh District, Tanah Datar Regency. This tourist attraction has great potential in terms of natural beauty, a strategic location on the shores of Lake Singkarak, and a sharia-based tourism concept. However, several obstacles have been identified in its management, such as limited public facilities, untrained human resources, and minimal promotion. This study uses a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. Data analysis was conducted using the SWOT method to formulate effective development strategies. The results of the study indicate that strategies are needed to strengthen digital promotion, add facilities such as a prayer room, public toilets, and a playground, train HR, and enhance cooperation with the local community and other tourism stakeholders. With these strategies, the Tambasa tourist attraction is expected to develop sustainably and make a positive contribution to the local economy.  Keywords: Development strategy, Tambasa tourism, SWOT, sustainable tourism